Eden Close : a novel - Shreve, Anita (Harcourt Brace Jovanovich, 1989)
After many years away, Andrew returns to his hometown to attend his mother's funeral. While there he is drawn into the tragic legacy of a childhood friend, Eden Close. Young and beautiful, Eden had sought the attention of Andrew's friends and acceptance from a mother who didn't want her. When the sounds of gunshots echoed through the town one night,however, Eden's life was changed forever. Now, seventeen years later, Andrew begins to unravel the layers of thwarted love in Eden's tormented family.